Screening of opportunistic Encephalitozoon intestinalis and Enterocytozoon bieneusi in immunocompromised patients in Slovakia - Halánová, Monika; Valenčáková, Alexandra; Jarčuška, Pavol; Halán, Miloš; Danišová, Oľga; Babinská, Ingrid; Dedinská, Kinga; Čisláková, Lýdia (Central European journal of public health, 2019)
OBJECTIVE: In recent years new infectious diseases, i.e. emerging or re-emerging diseases, have been coming to the forefront. Currently, microsporidia, considered to be a major cause of emerging and opportunistic infections particularly in immunocompromised individuals, are also included in this group. Therefore, the aim of our study was to map the prevalence of Encephalitozoon intestinalis and Enterocytozoon bieneusi infection in a group of patients and to compare it with the occurrence of specific antigens in immunocompetent people. METHODS: Detection of spores of both pathogens in faecal samples was performed by an immunofluorescence test using species-specific monoclonal antibodies. RESULTS: Positivity to E. intestinalis in 91 examined immunosuppressed patients reached 33% (30/91), while only 4.3% (3/70) of the control group samples were found to be positive (relative risk 7.7, p < 0.001). In case of E. bieneusi 14.3% (13/91) of immunocompromised patients were positive, as were 5.7% (4/70) of people from the control group (relative risk 2.5, p = 0.095). CONCLUSION: In case of development of any opportunistic infection, the infection is detected and removed in most cases at an early stage. The incidence of clinically manifested microsporidiosis in patients with immunodeficiency is rare as they are under constant medical supervision. However, we must not forget about opportunistic infections, and in case of any non-specific symptoms it is necessary to exclude or confirm the diagnosis for immediate treatment.
Keywords: Enterocytozoon; Feces; microsporidia; Opportunistic Infections; monoclonal antibodies; Encephalitozoonosis; immunocompromised patients; Microsporidiosis; Encephalitozoon intestinalis; Encephalitozoon; Slovakia; oportunní infekce; encephalitozoonóza; Mass Screening; Slovenská republika; feces; Humans; Enterocytozoon bieneusi; Immunocompromised Host; mikrosporidióza; plošný screening; lidé; imunokompromitovaný pacient